Corporate Reporting for the Professional Investor: What the Financial Analyst Wants to Know (Book). - Zeff, Stephen A. (The Accounting Review, 1965)
Reviews the book "Corporate Reporting for the Professional Investor: What the Financial Analyst Wants to Know," by Corliss D. Anderson.